23‐4: Research on LCD Strength Improvement Based on Neural Networks Algorithm - Sun, Yansheng; Liu, Wei; Deng, Yong; Zha, Guoping; Geng, Yuxu; Zhang, Zhi; Zhang, Dayu; Cheng, Yiming; Li, Yucheng; Yang, Sheng (SID International Symposium Digest of technical papers, 2024)
Aiming at the display fragmentation caused by insufficient module strength of ultra-thin and narrow design, a module strength prediction model is proposed to improve LCDs strength immunity and provide design guide, The comparison between the experiment measurement and the predicted results shows that the model can accurately predict the module strength under different design conditions and provide effective technical support and guidance.